MIXMASTER NUMERICAL BEHAVIOR AND GENERALIZATIONS - Ferraz, K.; Francisco, G. (American Physical Soc, 1992)
The numerical simulation of the mixmaster universe serves the purpose of suggesting two kinds of results. The intrinsic time evolution, during contraction, will be seen to be nonchaotic. This is a necessary feature of relativistic cosmological models undergoing this kind of motion. The mixmaster model also provides a clue on how to define chaoticity for systems described by nonautonomous sets of differential equations.